2014
DOI: 10.1097/mcc.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity cardiac troponin in acute conditions

Abstract: In all of these, elevated levels of high-sensitivity cTn are associated with increased mortality risk. In some of these, concepts are evolving as to how the pathophysiological signal of cardiomyocyte injury could be used to alter patient management and potentially improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…Recently, troponin T (TnT) has been recognized as a biomarker of myocardial injury. 1,2 Numerous reports have demonstrated that the measurement of high -sensitivity TnT (hs -TnT) levels may have prognostic value in various cardiovascular disorders, such as coronary artery disease (CAD), 3 heart failure, 4 and pulmonary embolism.…”
mentioning
confidence: 99%
“…Recently, troponin T (TnT) has been recognized as a biomarker of myocardial injury. 1,2 Numerous reports have demonstrated that the measurement of high -sensitivity TnT (hs -TnT) levels may have prognostic value in various cardiovascular disorders, such as coronary artery disease (CAD), 3 heart failure, 4 and pulmonary embolism.…”
mentioning
confidence: 99%
“…The septic patients can have an elevated cTn levels in the plasma in up to 60% of cases (Hamilton et al, 2012) in which its elevated levels is associated with increased mortality risk (Fromm, 2007; Gualandro et al, 2014). Septic patients with elevated cTn levels can have a 2–5 fold increased risk of death, even in the absence of known cardiovascular disease (Mantzouris et al, 2013).…”
Section: Non-invasive Methods To Assess Heart Function In Sepsismentioning
confidence: 99%
“…We identified potential risk factors of troponin release through a search of the literature [3,5,6,[12][13][14][15][16][17][18][19][20][21][22] and classified them according the following clusters: (A) patient-level risk factors present at baseline, and (B) three categories of time-dependent risk factors: (1) markers of inflammation and coagulation, (2) determinants of myocardial oxygen supply-demand mismatch, and (3) other potential causes of troponin release. All patient-level and most time-dependent risk factors had been prospectively recorded within the MARS study, yet some required additional retrospective review of the medical chart in order to yield accurate classifications.…”
Section: Data Collectionmentioning
confidence: 99%